Toxicity of ad lib. overfeeding: effects on cardiac tissue - Faine, L. A.; Diniz, Y. S.; Almeida, J. A.; Novelli, ELB; Ribas, B. O. (Elsevier B.V., 2002)
The aim of the present study was to determine the effects of ad lib, overfeeding and of dietary restriction (DR) on oxidative stress in cardiac tissue. Lipoperoxide concentrations ere decreased and antioxidant enzymes ere increased in moderate-DR-fed rats. Severe-DR induced increased lipoperoxide concentrations. Overfeeding increased lipoperoxide levels in cardiac tissue. Total superoxide dismutase (SOD) and Cu-Zn superoxide dismutase (Cu-Zn SOD) activities were decreased in cardiac tissue at 35 days of overfeeding. As no changes in glutathione peroxidase (GSH-Px) ere observed in overfed rats, awhile SOD and Cu-Zn SOD activities were decreased in these animals. it is assumed that superoxide anion is an important intermediate in the toxicity of ad lib, overfeeding. Overfeeding induced alterations in markers of oxidative stress in cardiac tissue. (C) 2002 Elsevier B.V. Ltd. All rights reserved.
Keywords: rat; reactive oxygen species; overfeeding; dietary restriction; heart